The risk of brexit : the politics of a referendum - Liddle, Roger (Rowman & Littlefield, 2015)
With the addition of substantial new material, this new edition charts how recent political developments have changed the debate surrounding Britain's membership of the European Union as a referendum on Brexit approaches.